MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA PAPAN JURANG PADA MATERI PENJUMLAHAN DAN PENGURANGAN BILANGAN CACAH DI KELAS II - Ruku, Iqdal Ade Putra; Kudus, Kudus; Aries, Nur Sakinah; Marshanawiah, Andi; Pakaya, Widi Candika (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
This research aimed to improve student learning outcomes through the application of the Problem-Based Learning (PBL) model assisted by the papan jurang learning media on the topic of addition and subtraction of whole numbers in Grade II of SDN 1 Telaga Biru. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, in which each cycle consisted of planning, implementation, observation, and reflection with 20 students as subjects. Data were collected through learning outcome tests, observations of teacher and student activities, and documentation, and were analyzed using descriptive, quantitative, and qualitative methods. The results showed an improvement in students' learning outcomes on the topic of addition and subtraction of whole numbers after the implementation of the Problem-Based Learning (PBL) model and the papan jurang media. In the initial condition (pre-cycle), only 20% of students achieved the minimum mastery criterion (score ≥75). Following the implementation of Cycle I, the mastery learning rate increased to 55%, with 11 students achieving mastery. In Cycle II, learning outcomes continued to improve, with 90% of students achieving mastery (18 students). In addition, observations indicated an increase in student activity from the moderate category in the pre-cycle to the very good category in Cycle II. Thus, it can be concluded that the application of the Problem-Based Learning (PBL) model assisted by the papan jurang media can effectively improve student learning outcomes in addition and subtraction of whole numbers topic in Grade II of SDN 1 Telaga Biru. ABSTRAK Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa melalui model problem based learning (PBL) berbantuan media papan jurang pada materi penjumlahan dan pengurangan bilangan cacah di kelas II SDN 1 Telaga Biru. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) model Kemmis & Mc Taggart yang setiap siklusnya terdiri dari tahap perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian adalah 20 siswa. Data diperoleh melalui tes hasil belajar, observasi aktivitas guru dan siswa, serta dokumentasi, kemudian dianalisis secara deskriptif kuantitatif dan kualitatif.Hasil penelitian menunjukkan adanya peningkatan hasil belajar siswa pada materi penjumlahan dan pengurangan bilangan cacah setelah penerapan model problem based learning (PBL) dan media papan jurang. Pada kondisi awal (pra-siklus) hanya 20% siswa yang mencapai KKM (nilai ≥ 75). Setelah tindakan pada siklus I, ketuntasan meningkat menjadi 55% dengan 11 siswa tuntas. Pada siklus II, hasil belajar semakin meningkat dengan ketuntasan 90% (18 siswa tuntas). Selain itu, observasi menunjukkan peningkatan aktivitas siswa dari kategori cukup pada pra-siklus menjadi kategori sangat baik pada siklus II. Dengan demikian, dapat disimpulkan bahwa penerapan model problem based learning (PBL) berbantuan media papan jurang dapat meningkatkan hasil belajar siswa pada materi penjumlahan dan pengurangan bilangan cacah di kelas II  SDN 1 Telaga Biru.